Italian Public Policy Against the Mafia - Maria Shibkova; Daria Nedelnichenko (Современная Европа)
The Mafia phenomenon in Italy starting the 19th century has managed to penetrate into many spheres of life in Italian society, such as politics, economics, culture and even sports. The history of the development of the political system in Italy is non-linear, over the last century and a half it has included at least three periods: liberal-monarchical, authoritarian and the current one, republican-democratic. These constant transformations and instability of the political system were used by the mafia. Remaining unpunished for a long time, mafia organizations seriously undermined the security of the Italian society through illegal human trafficking, drug trafficking, kidnappings and murders. Nevertheless, in the second half of the twentieth century, the political system began to react to the Mafia, trying to solve the problem of organized crime. One of the most important tools on the way to solve this problem is the development of a legislative framework to combat organized crime. Therefore, the aim of this study is to examine the main milestones in the development of anti-mafia legislation in Italy and to evaluate its effectiveness. Using the case study method, the authors note that the formation took place in a wave-like manner. The greatest intensity was observed in the 1960s, 1980s and in the 1990s, when the foundations of the modern anti-mafia legislation were laid, in the XXI century these norms were only expanded and improved. The authors come to the conclusion that the authorities' actions against the mafia were subject to a certain pattern: in the absence of high-profile crimes there was inaction of the political system interrupted only against the background of high-profile crimes. It was only at the beginning of the new millennium that the government shifted from a repressive to a preventive strategy. Nevertheless, the accumulated body of legal norms and statistics indicate significant progress of the state in the fight against the mafia.